Ted Benton, Ian Craib, Philosophy of social science.The philosophical foundations of social thought - Σκομβούλης, Μιχάλης (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]